Revealed preferences for policy experiments - Chlond, Bettina; Goeschl, Timo; Lohse, Johannes (AWI discussion paper series, 2025)
Randomized controlled trials remain underutilized in informing policy design, despite their potential. Moral objections to experimentation ("experiment aversion") have been proposed as an explanation. We present three studies with members of the general public and policy-makers that allow us to measure and compare moral approval, stated preferences as well as revealed preferences for policy experimentation, within the overarching context of a public assistance program. We find that evidence based on moral approval systematically underestimates revealed preferences for policy experimentation due to conceptual misalignment and hypothetical bias. People and policy-makers trade off possible moral objections against the benefits of policy experimentation.
Keywords: Graue Literatur